Analysis and Mitigation of the Narrowband Interference Impact on IR-UWB Communication Systems. (13th March 2012) - Shaheen, Ehab M.; El-Tanany, Mohamed
Abstract : The impact of narrowband interference signals on impulse radio ultrawideband (UWB) communication systems has been investigated. A closed form expression for the bit error rate performance of UWB communication system in a Log-normal flat fading channel under such impact is evaluated. The actual UWB channel model is known as a multipath fading channel; however flat fading channel model can be considered with some of the UWB wireless applications such as UWB wireless sensor networks which are characterized by size and energy constraints. Thus, a simple and low-cost one-finger Rake receiver can be used with such wireless systems. It was proven that UWB systems unavoidably suffer from the interference caused by the coexisting systems due to the restraint on their transmission power levels. To this end, we propose an interference canceller scheme which is capable of suppressing the impact of such interference and enhancing the performance of UWB communication systems. The interference canceller scheme performance is also investigated in various scenarios of operation such as the presence of multiple narrowband interference signals, symbol timing error, and a comparison with a notch filter-based case.